1998
DOI: 10.1002/(sici)1096-9071(199811)56:3<179::aid-jmv1>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Antibody against the Epstein-Barr virus BHRF1 protein, a homologue of Bcl-2, in patients with nasopharyngeal carcinoma

Abstract: The Epstein-Barr virus (EBV) open reading frame BHRF1, a homologue of the oncogene bcl-2, was cloned from a patient with nasopharyngeal carcinoma (NPC) and overexpressed in Escherichia coli. The resulting recombinant BHRF1 fusion protein, with an apparent molecular weight of 35 KD, was used as antigen in an immunoblotting assay for IgG antibody in human sera. Anti-BHRF1 antibody was detected in 57 (61.3%) of 93 patients with NPC, 5 (5.7%) of 87 patients with nonmalignant diseases of the nasopharynx, and in 1 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Further studies indicated that antibodies against EBV could be useful markers for the early detection of NPC patients (Henle and Henle, 1976;Zeng et al, 1982). In our laboratory, we have examined the antibodies against EBV DNase, DNA polymerase, thymidine kinase, major DNA binding protein, BHRF1, viral capsid antigen (VCA) and ENBA1 in patients and controls, and found that all these antibodies could be useful markers for the detection of NPC (Chen et al, 1982(Chen et al, , 1985(Chen et al, , 1989Liu et al, 1989Liu et al, , 1997Liu et al, , 1998Hsu et al, 1992). Among these was a prospective study carried out between 1983 and 1986 to examine the antibodies against EBV DNase and VCA in the inhabitants of NPC high-risk areas in Taiwan (Chen et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Further studies indicated that antibodies against EBV could be useful markers for the early detection of NPC patients (Henle and Henle, 1976;Zeng et al, 1982). In our laboratory, we have examined the antibodies against EBV DNase, DNA polymerase, thymidine kinase, major DNA binding protein, BHRF1, viral capsid antigen (VCA) and ENBA1 in patients and controls, and found that all these antibodies could be useful markers for the detection of NPC (Chen et al, 1982(Chen et al, , 1985(Chen et al, , 1989Liu et al, 1989Liu et al, , 1997Liu et al, , 1998Hsu et al, 1992). Among these was a prospective study carried out between 1983 and 1986 to examine the antibodies against EBV DNase and VCA in the inhabitants of NPC high-risk areas in Taiwan (Chen et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…These were based on antibodies to different antigenic components of the EBV (9,(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). Attempts to use panels of antibody-based markers have generally been useful in improving the accuracy of NPC detection (13, 15, 20, 21, 29 -32 ).…”
mentioning
confidence: 99%
“…Such cross-reactive potential explains why higher the anti-EBV IgG antibody titer, worse may be the disease prognosis and faster the disease progression as described by a continuum of reports since the 1970s. [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] That is, autoimmunity is not a matter of "rare immunological holes," but it is intrinsic to the immune response that involves most of the human proteome by being most of the human proteome shared with microbial entities as a result of a long evolutionary path that from viruses and bacteria led to the eukaryotic cell. 180 In conclusion, this study highlights the necessity of reviewing the hypothesis of the "negative selection" of self-reactive lymphocytes and, at the same time, emphasizes the importance of the "peptide uniqueness" concept to develop immunotherapies against EBV infection, and infections in general.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12][13][14] At the same time, anti-EBV antibody level was found to be higher in BL patients than in control subjects. 3,[15][16][17] High level of anti-EBV immunoglobulin G antibodies were also found in subjects with NPC, [18][19][20][21] with IgG reactivity increasing significantly with tumor stage 21 ; Hodgkin and non-Hodgkin lymphomas [22][23][24] ; precancerous gastric lesions 25 ; MS [26][27][28][29] ; RA [30][31][32] ; MG 33,34 ; and SLE, 29,31,34 among others. In general, high antibody titers to EBV appeared to be related to a worse prognosis, a phenomenon that has been described by Coutinho's laboratory 35 as "the advantage of being low-respondents."…”
Section: Introductionmentioning
confidence: 99%